2013
DOI: 10.1007/s00268-012-1900-x
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Net Mesh for Abdominal Wall Hernioplasty: A Comparison of Material Characteristics with Commercial Prosthetics

Abstract: The material and mechanical properties of the polyethylene mosquito net are substantially equivalent to those of commonly used lightweight commercial meshes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 35 publications
1
30
0
1
Order By: Relevance
“…This has been confirmed by a meta-analysis, which also demonstrated no increase in septic complications [36]. Subsequent studies have suggested that mosquito nets might actually be better in terms of bursting strength and anisotropy than commercial products in terms of retraction of the mesh [37]. …”
Section: Introductionmentioning
confidence: 84%
“…This has been confirmed by a meta-analysis, which also demonstrated no increase in septic complications [36]. Subsequent studies have suggested that mosquito nets might actually be better in terms of bursting strength and anisotropy than commercial products in terms of retraction of the mesh [37]. …”
Section: Introductionmentioning
confidence: 84%
“…The use of this alternative mesh requires correct preparation, including sterilization. 22 Preparation and distribution of the mesh to surgical facilities must be carefully monitored, and facilities must incorporate training and education of surgeons and staff and quality assessment in order to minimize adverse events. The meticulous attention to these details in the current study is not routine in the general health care system in most countries.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Mosquito meshes, which are similar to commercial meshes, are currently used in some places as a low-cost alternative in hernia repair. [19][20][21][22][23] Previous studies on the use of mosquito mesh in groin hernia repair have shown promising results with respect to tissue reaction, outcome, and cost-effectiveness. 19,[21][22][23][24][25][26] However, data from randomized trials are lacking to inform the safety and long-term effectiveness of this practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A commercial mesh costs $125·0 (€118·3) in Uganda today. The structure of the mosquito mesh has been described in detail previously and compared with other commercial meshes.…”
Section: Methodsmentioning
confidence: 99%